2018
DOI: 10.14710/reaktor.18.2.108-112
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVEMENT OF BIOETHANOL PRODUCTION BY USING Saccharomyces cerevisiae [Meyen ex E.C. Hansen] IMMOBILIZED ON PRETREATED SUGARCANE BAGASSE

Abstract: Pretreated of sugarcane bagasse was used as a carrier for immobilization of Saccharomyces cerevisiae. Pretreatments were carried out by steaming, pressurized steam, and combination both of procedure. The objectives of this research was to investigate the effect of pretreatment on sugarcane bagasse to cells adsorption and bioethanol production. Immobilization process was conducted in a ratio of 2.5 g carrier/50 mL cell suspension. Whole cell biocatalyst as much as 1% (w/v) was used as inoculum for bioethanol fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The results obtained in this study were also corroborated by the SEM data which demonstrated bunching of yeast cells on the surface of untreated SB fibers (Fig. 4(a)) where cells were immobilized more effectively 10 . After the immobilization process, cells attached through the pores and formed colonies.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The results obtained in this study were also corroborated by the SEM data which demonstrated bunching of yeast cells on the surface of untreated SB fibers (Fig. 4(a)) where cells were immobilized more effectively 10 . After the immobilization process, cells attached through the pores and formed colonies.…”
Section: Resultssupporting
confidence: 85%
“…Pretreatment resulted in lignin removal which ultimately made the structure of SB fragile 15 and hence cell retention decreased significantly on pretreated SB. In an earlier work, SB was prepared for immobilization by steam pretreatment 10 . However, the requirement of high temperature and compatible reactors limit the application of steam treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations